The Cambridge companion to Milton - Danielson, Dennis (Cambridge companions to literature, 1999)
Milton's social life / Stephen B. Dobranski Milton's Ludlow masque / Cedric Brown 'Lycidas' / J. Martin Evans 'Poems 1645': the future poet / Colin Burrow Milton's politics / Martin Dzelzainis Milton's prose / Thomas N. Corns Milton's sonnets and his contemporaries / R. F. Hall The genres of 'Paradise Lost' / Barbara Kiefer Lewalski Language and knowledge in 'Paradise Lost' / John Leonard The Fall and Milton's theodicity / Dennis Danielson Milton's Satan / John Carey Milton and the sexes / Diane K. McColley Milton and the reforming spirit / Georgia Christopher How Milton read the Bible: the case of 'Paradise Regained' / Mary Ann Radzinowicz Reading 'Samsom Agonistes' / Joan S. Bennett Milton's readers / Nicholas von Maltzahn Miltonj's place in intellectual history / William Kerrigan Milton's works and life: select studies and resources / R. G. Siemens